2014
DOI: 10.1007/s11434-014-0335-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy and light meson wavefunctions

Abstract: We present a short review on the properties of heavy and light mesons' light-cone wavefunctions (LCWFs), and their distribution amplitudes (DAs). The B meson LCWFs can be treated by taking the heavy quark limit (m b → ∞) and by using the heavy quark effective theory. Furthermore, we propose a simple model for the B meson WFs with 3-particle Fock states' contributions, whose behaviors are controlled by two parametersΛ and δ. Using such model, the form factors F

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 127 publications
(225 reference statements)
1
21
0
Order By: Relevance
“…[98], the authors studied the rapidity resummation improved B meson wave function and found that the resummation effect keeps the normalization of the B meson wave functions and strengths their convergent behavior at small spectator momentum. For more details about the wave functions of B/B s meson, one can see a new review paper [99] and references therein. We here still use the B/B s wave functions as defined in Refs.…”
Section: 1mentioning
confidence: 99%
“…[98], the authors studied the rapidity resummation improved B meson wave function and found that the resummation effect keeps the normalization of the B meson wave functions and strengths their convergent behavior at small spectator momentum. For more details about the wave functions of B/B s meson, one can see a new review paper [99] and references therein. We here still use the B/B s wave functions as defined in Refs.…”
Section: 1mentioning
confidence: 99%
“…Additional model approaches exist, see Refs. [54][55][56][57] for instance. A heavy-light LCDA was also extracted from the extrapolation of Bethe-Salpeter amplitudes calculated with an unphysical pion mass [58].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, one can write down H (0) a directly by using the initial and the final pion meson wave functions [10,[29][30][31][32][33] as given explicitly in Eqs. (10), (11) with the chiral mass of pion m 0π = 1.74 GeV:…”
Section: Leading Order Space-like Scalar Pion Form Factormentioning
confidence: 99%